IUBMB focused meeting: 10thconference Inhibitors of Protein Kinases. Kinase inhibitors in target biology and disease (IPK2019). Issue 6 (22nd May 2020) - Poznanski, Jaroslaw; Fabbro, Doriano
Abstract: The 10 th jubilee conference (IPK2019) took place on September 15–19, 2019 in Warsaw, on the Ochota campus as the IUBMB Focused Meeting entitled "Inhibitors of Protein Kinases. Kinase inhibitors in target biology and disease".